1978
DOI: 10.1021/jo00399a033
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of tertiary glycidamides with boron trifluoride etherate. Evaluation of the potential for rearrangement with amide group migration

Abstract: with TLC on silica gel with dimethylformamide (Rf 0.9) or aqueous 80% methanol (Rf 0.8). Attempted recrystallization usually resulted in partial decomposition, as shown by TLC. The analytical sample was dried for 9 h at 0.1 Torr at 100 °C. The compound darkened above 240 °C but did not melt up to 400 °C; 100-MHz !H NMR (Me2SO-d8) 8.55 (s, 1, NCHN), 8.10 (s, 1, CH=CB2), 7.64 (broadened s, 1, NH), 7.18 (broadened s, 1, NH), 3.42 (s, ~10, NH, BOH, and H20 from solvent); on addition of methanol dropwise, the 7.64… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 4 publications
(12 reference statements)
2
8
0
Order By: Relevance
“…13 C NMR (100 MHz, CDCl 3 ): δ = 173.5, 139.2, 138.3, 129.8, 128.6, 128.4, 128.3, 127.2, 124.2, 115.2, 72.3, 54.6, 30.5, 26.8 ppm. The spectroscopic data of 21 were identical to those of the authentic material that was previously reported 8…”
Section: Methodssupporting
confidence: 76%
See 1 more Smart Citation
“…13 C NMR (100 MHz, CDCl 3 ): δ = 173.5, 139.2, 138.3, 129.8, 128.6, 128.4, 128.3, 127.2, 124.2, 115.2, 72.3, 54.6, 30.5, 26.8 ppm. The spectroscopic data of 21 were identical to those of the authentic material that was previously reported 8…”
Section: Methodssupporting
confidence: 76%
“…The further conversion of 18 into 1,3,3,4‐tetrasubstituted 21 was achieved by N ‐methylation with CH 3 I and Cs 2 CO 3 . The relative configuration of trans ‐ 21 was assigned by comparing the NMR data with those previously reported for the authentic compound 8. The subsequent reduction of 18 with LiAlH 4 afforded trans ‐ 22 in 77 % yield with a 92:8 er , and, thus completed the synthetic sequence.…”
Section: Resultsmentioning
confidence: 85%
“…Using BF 3 OEt 2 as the catalyst, qualitative observations suggested that the thioester group 12,13 migrated substantially faster than the ester in that system, but the amide was very sluggish and refused to rearrange at all except for a small amount in one compound 14 .…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the base was then investigated and it was found that the use of other bases, such as potassium carbonate, triethylamine, potassium acetate, sodium methoxide or potassium phosphate, were inferior to cesium carbonate (entries [5][6][7][8][9]. Screening revealed that the use of ethanol as solvent gave identical results to those obtained in methanol (entry 10), but other solvents, including isopropanol, tetrahydrofuran, N,N-dimethylformamide, acetonitrile, and toluene, were less efficient (entries [11][12][13][14][15].…”
mentioning
confidence: 99%
“…With the optimal reaction conditions in hand, the scope of the reaction was investigated with a range of iodoethynes and arylboronic acids (Table 2). Initially, a variety of arylboronic acids 2b-m were investigated by their reaction with 3-iodo-N-methyl-N-phenylpropiolamide (1a; entries [1][2][3][4][5][6][7][8][9][10][11][12]. The results demonstrated that the optimal conditions were general for arylboronic acids, and were compatible with several functional groups, including methyl, methoxy, fluoro, chloro, iodo, formyl, acetyl, nitro, and vinyl groups, on the aryl moiety.…”
mentioning
confidence: 99%